PATHOGENICITY OF Fusarium graminearum ON CREOLE BEANS: GERMINATION, VIGOR AND SEEDLING DAMAGE - Divensi, Luan Junior; Brandler, Daiani; Barro, Jhonatan Paulo; Stempkowski, Lucas Antonio; Mendes Milanesi, Paola (REVISTA DE AGRICULTURA, 2019)
The objective of this study was to evaluate the pathogenicity of Fusarium graminearum by creole bean seeds, quantify the incidence of root lesions and damping off in seedlings, and, evaluate the reduction of germination and seed vigor. Two varieties of creole beans, ‘Cavalo’ and ‘Chumbinho’, were collected from a family property located in the municipality of Severiano de Almeida, RS. The treatments evaluated were: seeds not inoculated (T1) and inoculated (T2) with F. graminearum macroconidia suspension at a concentration of 8.0 x 105 macroconidia mL-1, and was observed the appearance of lesions and the influence on vigor and germination. The variety ‘Cavalo’ proved to be more susceptible to F. graminearum, expressing vigor reduction, incidence of root lesions and damping off. The variety ‘Chumbinho’ expressed no vigor reduction, although it has occurred reduced incidence of damping off. With respect to root lesions, the 'Chumbinho' variety compares to the variety ‘Cavalo’.